TRAGEDY IN THE MOVIE 200 METERS BY AMEENA NAYFEH, USING ROMAN JACOBSON`S SEMIOTIC THEORY - Ayu Safitri Rezeuki; Zulkhairi; Anshar Zulhelmi (Hijai - Journal on Arabic Language and Literature, 2025)
This study examines the tragedy in Ameen Nayfeh's film 200 Meters (2020) using Roman Jakobson's semiotic communication model, namely code and message. This model emphasizes six factors of communication—addresser, addressee, message, context, code, and contact—which are interconnected in constructing meaning. This film tells the story of Mustafa, a Palestinian father who struggles to reunite with his family despite being separated by the Israeli separation wall. Through Jakobson's framework, the analysis shows how the sender (characters and director), receiver (audience), and messages about separation, injustice, and resilience are constructed and conveyed in a specific socio-political context. The study found that 200 Meters represents tragedy not only on a personal level, but also on a collective dimension, symbolizing the Palestinian people's experience of isolation and limited freedom.